2005
DOI: 10.1007/s10384-004-0182-8
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Upbeat to Downbeat Nystagmus Observed in a Patient with Wernicke’s Encephalopathy

Abstract: Owing to an underlying central vestibular imbalance, even after the recovery of acute neurological symptoms, Wernicke's encephalopathy can be complicated by persistent downbeat nystagmus, which can be treated by a GABA agonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Differential diagnostic considerations in patients with ataxia and affection of the ocular motility includes Wernicke`s encephalopathy as well as paraneoplastic neurological syndromes (PNS). Wernicke`s encephalopathy is due to nutritional deficiencies especially thiamine deficiency, and vertical nystagmus has been reported in patients with this condition [6]. Our patient had no history of alcohol abuse or malnutrition making this diagnosis less likely.…”
Section: Discussionmentioning
confidence: 84%
“…Differential diagnostic considerations in patients with ataxia and affection of the ocular motility includes Wernicke`s encephalopathy as well as paraneoplastic neurological syndromes (PNS). Wernicke`s encephalopathy is due to nutritional deficiencies especially thiamine deficiency, and vertical nystagmus has been reported in patients with this condition [6]. Our patient had no history of alcohol abuse or malnutrition making this diagnosis less likely.…”
Section: Discussionmentioning
confidence: 84%
“…The systemic administration of clonazepam, a gamma-aminobutyric acid (GABA) agonist, may be effective in suppressing nystagmus symptoms, especially the appearance of primary position DN. In a previous case report, the authors explained that the suppressive effects of a GABA agonist on longstanding DN suggest that these abnormal eye movements are caused by a GABA inhibitory dysfunction in the central vestibular system [18]. This study had several limitations.…”
Section: Video Segmentmentioning
confidence: 82%
“…One case report described UN due to posterior medullary hemorrhage and suggested that an underlying central vestibular imbalance may cause the transition from UN to DN [15]. A separate case report of WE showed a transition from transient UN to permanent DN over a period of months and suggested that the transition was caused by the predominant difference in vertical velocity induced by gravity [18]. Another study explained that the transition from DN to UN caused by 4-aminopyridine may be associated with the augmentation of the physiological inhibitory influence on cerebellar nuclei neurons [20].…”
Section: Video Segmentmentioning
confidence: 99%
“…In support of the latter, in follow-up months later, spontaneous downbeat nystagmus (DBN) was seen, and it was noted that changes in head orientation relative to gravity (head tilt and supine position) transitioned his DBN to UBN, a feature that can be seen with utricle pathway damage. 1 Overall, in our patient's case, ocular motor signs would be best explained by involvement of the perihypoglossal nuclei (UBN and GEN), paramedian tract cell groups, or their connections with the vestibulocerebellum (DBN), and vestibular nuclei (causing SCC and utricle imbalance, right more than left-sided dysfunction given skew deviation with left hypertropia and LBN).…”
mentioning
confidence: 80%